Study of the relationship of genetic polymorphism of SLC27 gene, fatty acid transport protein, with some economic parameters and carcass characteristics of broilers - Ail Ahmed Abdul-Kareem; Ail moh jaf falh (University of Thi-Qar Journal of agricultural research, 2022)
This study was conducted in the poultry field of the College of Agriculture and the Marshes - University of Dhi Qar for the period from 10/11/2021 to 26/12/2021 in cooperation with the Molecular Genetics Laboratories at the Marsh Research Center - College of Agriculture and Marshes for the purpose of the effect of multiple genotypes of the FATP gene on productive performance and some traits Physiology of broilers of ROSS 308 strain, 150 birds were used in this study. The results of this study showed the following.The results were analyzed by the sequence of nitrogenous bases of the gene studied outside Iraq by the South Korean company, Macrogen corporation-Korea. Carcass weight, dressing ratio, relative weight of the studied cuts Three genotypes were diagnosed, the first being GG, GA and AA, and there were significant significant differences (P<0.05)) in the distribution ratios of the genotypes of the FATP gene according to the mutation G237A, where the GA genotype recorded the highest percentage, followed by the GG genotype, and then followed by the AA genotype Its proportions were 0.49, 0.39 and 0.12, respectively, and the G allelic frequency is superior to the A allele, as it reached 0.64 and 0.36, respectively, and it was noted that there were no significant differences for the genotypes of the G237A mutation in the weekly body weights, as it was found that there are no significant differences between the genotypes GA, GG and AA gene FATP in the average live body weight on the first day of life of the bird and the second, third, fourth and fifth weeks, The results showed that there was a significant difference (P<0.05) for the genotypes of the G237A mutation in the average carcass weight, as the AA genotype was superior to the GG and GA genotypes. As for the relative weight of the wings, the AA genotype was superior to the GA and GG genotypes, while the relative weight characteristic of the leg was superior to Structure AA on the genotypes GG and GA There was no significant effect of the relative weights of the thighs with the drum stick, wings, neck, back and belly fat INTRODUCTIONThe poultry industry at the present time is characterized by the increase in both production and the high efficiency of birds in converting the consumed feed into meat and eggs, as the main direction for the development of this industry now and in the future is always to improve the productive value (wiseman & Garnsworthy 2001). Some genetic selection, different variants represent a valuable source of protein, vitamins and minerals & cnningham (Demby, 2002) as the percentage of protein in poultry meat is about (5%) (Insr et al., 2006). The next episode was completed in the next episode, and a member of body fat (Simopoulos et al., 1998) Fat deposition is the most important axis for broilers, which is an important aspect in the development of genetic maps, as it is one of the important characteristics that have a direct relationship in determining the quality and quality of meat produced in the world, but in recent years, abdominal fat deposition has become one of the main physiological problems facing the poultry industry as well as reduce The overall production efficiency because it reduces the quality of carcasses and their products and on the other hand affects the consumption of poultry meat as a result of the effect of fat deposition on the health of the consumer (Kahraman et al., 2004)Therefore, the current study aimed to reveal the multiple genetic phenotypes of the FATP1 gene, the fatty acid transport protein, and its relationship to some economic criteria and carcass characteristics for broilers type ROSS 308) using the technique of deficient DNA sequencing.